The Rooster Bar - Grisham, John (London : Hodder & Stoughton, 2025)
"Mark, Todd, and Zola came to law school to change the world, to make it a better place. But now, as third-year students, these close friends realize they have been duped. They all borrowed heavily to attend a third-tier, for-profit law school so mediocre that its graduates rarely pass the bar exam, let alone get good jobs. And when they learn that their school is one of a chain owned by a shady New York hedge-fund operator who also happens to own a bank specializing in student loans, the three know they have been caught up in The Great Law School Scam. But maybe there's a way out. Maybe there's a way to escape their crushing debt, expose the bank and the scam, and make a few bucks in the process. But to do so, they would first have to quit school. And leaving law school a few short months before graduation would be completely crazy, right? Well, yes and no" --
Keywords: Law students -- Fiction; Student loans -- Fiction; Law schools -- Fiction; FICTION -- Thrillers -- Crime; FICTION -- Thrillers -- Legal; FICTION -- Thrillers -- Suspense; Law students -- Fiction; Student loans -- Corrupt practices -- Fiction; Law schools -- Corrupt practices -- Fiction; Fiction